FOSTERING BETTER READING COMPREHENSION IN JUNIOR HIGH SCHOOL STUDENTS: EXPLORING PRE-READING ACTIVITIES AND INTEREST LEVELS - Ratmanida; Nindi Oktriyani (Indonesian EFL Journal, 2025)
This study aims to determine the effect of using pre-reading activities and reading interest on students reading comprehension. The study categorized as an experimental research. The population of the research was eighth grade students in the academic years 2024/2025. In this study, the experimental class was taught using pre-reading activities, while the control class was taught using another pre-reading activities. Before being given treatment, both classes were given pre-test to find out the extent of students’ comprehension of the text. After being given treatment, students are given post-test. Meanwhile, the questionnaire was only given at the beginning of the meeting. The instruments in this study are reading comprehension tests and reading interest questionnaires. For each instruments totaled 30 items. The data collection was done by giving reading interest questionnaire and a reading comprehension test (pre and post test) after six meetings of treatments. The data analysis was done by applying a T-test and a two-way ANOVA to test the hypothesis. Furthermore, in the experimental class there were 29 students who had a high interest in reading and 1 student who had a low interest in reading. Meanwhile, in the control class, there were 26 students who had a high interest in reading and 4 students who had a low interest in reading. It can be concluded that H0 was rejected and Ha was accepted, which shows that there is a significant difference between the experimental class taught using pre-reading activities and the control class taught without using pre-reading activities on reading comprehension. Therefore, it can be concluded that pre-reading activities are one of the effective strategies to improve students' reading comprehension and reading interest. Keywords: Pre-Reading Activities;Readimg Comprehension; Reading Interest.